Influence of serum iron test results on the diagnosis of iron deficiency in children: a retrospective observational study. Issue 7 (5th July 2021) - Sezgin, Gorkem; Li, Ling; Westbrook, Johanna; Wearne, Elisabeth; Azar, Denise; McLeod, Adam; Pearce, Christopher; Ignjatovic, Vera; Monagle, Paul; Georgiou, A
Abstract : Background and objective: Serum iron results are not indicative of iron deficiency yet may be incorrectly used to diagnose iron deficiency instead of serum ferritin results. Our objective was to determine the association between serum iron test results and iron-deficiency diagnosis in children by general practitioners. Design, setting, patients and main outcome measures: A retrospective observational study of 14 187 children aged 1–18 years with serum ferritin and serum iron test results from 137 general practices in Victoria, Australia, between 2008 and 2018. Generalised estimating equation models calculating ORs were used to determine the association between serum iron test results (main exposure measure) and iron-deficiency diagnosis (outcome measure) in the following two population groups: (1) iron-deplete population, defined as having a serum ferritin <12 µg/L if aged <5 years and <15 µg/L if aged ≥5 years and (2) iron-replete population, defined as having a serum ferritin >30 µg/L. Results: 3484 tests were iron deplete and 15 528 were iron replete. Iron-deplete children were less likely to be diagnosed with iron deficiency if they had normal serum iron levels (adjusted OR (AOR): 0.73; 95% CI 0.57 to 0.96). Iron-replete children had greater odds of an iron-deficiency diagnosis if they had low serum iron results (AOR: 2.59; 95% CI 1.72 to 3.89). Other contributors to an iron-deficiency diagnosis were female sex and having anaemia. Conclusion: Serum ferritin alone remains the best means of diagnosing iron deficiency. Reliance on serum iron test results by general practitioners is leading to significant overdiagnosis and underdiagnosis of iron deficiency in children.